Gold Nanoparticle-Photosensitizer Conjugate Based Photodynamic Inactivation of Biofilm Producing Cells: Potential for Treatment of C. albicans Infection in BALB/c Mice. - Mohd Asif Sherwani (PLoS ONE, 2015)
Photodynamic therapy (PDT) has been found to be effective in inhibiting biofilm producing organisms. We investigated the photodynamic effect of gold nanoparticle (GNP) conjugated photosensitizers against Candida albicans biofilm. We also examined the photodynamic efficacy of photosensitizer (PS) conjugated GNPs (GNP-PS) to treat skin and oral C. albicans infection in BALB/c mice.The biomimetically synthesized GNPs were conjugated to photosensitizers viz. methylene blue (MB) or toluidine blue O (TB). The conjugation of PSs with GNPs was characterized by spectroscopic and microscopic techniques. The efficacy of gold nanoparticle conjugates against C. albicans biofilm was demonstrated by XTT assay and microscopic studies. The therapeutic efficacy of the combination of the GNP conjugates against cutaneous C. albicans infection was examined in mouse model by enumerating residual fungal burden and histopathological studies.The GNP-PS conjugate based PDT was found to effectively kill both C. albicans planktonic cells and biofilm populating hyphal forms. The mixture of GNPs conjugated to two different PSs significantly depleted the hyphal C. albicans burden against superficial skin and oral C. albicans infection in mice.The GNP-PS conjugate combination exhibits synergism in photodynamic inactivation of C. albicans. The GNP conjugate based PDT can be employed effectively in treatment of cutaneous C. albicans infections in model animals. The antibiofilm potential of PDT therapy can also be exploited in depletion of C. albicans on medical appliances such as implants and catheters etc.